Comparative evaluation of cleaning efficacy of self-adjusting file and waveone file: An in vitro scanning electron microscopic study - Balakrishnan Bakthavatchalam; Muthukrishnan Sudharshana Ranjani; Krishnan Amudhalakshmi (Wolters Kluwer Medknow Publications, 2019)
Aim: This study aims to compare the cleaning efficacy of root canal walls using two rotary single file systems: self-adjusting file (SAF) and WaveOne (WO). Materials and Methods: Forty extracted human premolars with similar range of canal curvature were selected, decoronated, working length determined and roots were divided into two groups of 20 samples each: Group I - SAF and Group II - WO. All root canals were irrigated with 3% sodium hypochlorite (NaOCl) and 17% ethylenediaminetetraacetic acid (EDTA).The roots were sectioned longitudinally and subjected to scanning electron microscopic examination. The amount of debris and smear layer was evaluated using five score index at coronal, middle and apical third levels. Statistical analysis was performed using the Chi-square test and significance was set at a P < 0.05. Results: Statistically significant difference was observed between the groups in cleaning the apical third. Group I (SAF) showed better canal cleanliness compared to Group II (WO) in the apical third. Conclusion: Within the limitations of this study, SAF in combination with 3% NaOCl and 17% EDTA irrigating solution had significantly better cleaning efficacy in the apical third of root canals when compared to WO rotary file system.